Linkage disequilibrium in Angus, Charolais, and Crossbred beef cattle - Lu, Duc; Sargolzaei, Mehdi; Kelly, Matthew; Li, Changxi; Vander Voort, Gord; Wang, Zhiquan; Plastow, Graham; Moore, Stephen; Miller, Stephen (Frontiers in Genetics, 2012)
Linkage disequilibrium (LD) and the persistence of its phase across populations are important for genomic selection as well as fine scale mapping of quantitative trait loci. However knowledge of LD in beef cattle, as well as the persistence of LD phase between crossbreds and purebreds, is limited. The objective of this study was to understand the patterns of LD in Angus, Charolais, and crossbred beef cattle based on 31’073, 32’088 and 33’286 SNP in each population, respectively. Amount of LD decreased rapidly from 0.29 to 0.23 to 0.19 in Angus (AN), 0.22 to 0.16 to 0.12 in Charolais (CH), 0.21 to 0.15 to 0.11 in Crossbreds (C), when the distance range between markers changed from 0-30kb to 30-70kb and then to 70-100kb, respectively. Breeds and chromosomes had significant effects (P<0.001) on LD decay. There was significant interaction between breeds and chromosomes (P<0.001). Correlations of LD phase were high between C and AN (0.84), C and CH (0.81), as well as between AN and CH (0.77) for distances less than or equal to 70kb. These dropped when the distance increased. Estimated effective population sizes for AN and CH were 207 and 285, respectively, for 10 generations ago. Given a useful LD of at least 0.3 between pairs of SNPs, the LD phase between any pair of the three breed groups was highly persistent. The current SNP density would allow the capture of approximately 49% of useful LD between SNP and marker QTL in Angus, and 38% in Charolais. A higher density SNP panel or redesign of the current panel is needed to achieve more of useful LD for the purpose of genomic selection beef cattle.